Penggunaan SQL Server dalam Pengolahan Data Warehouse yang Praktis dan Berkelanjutan - Kuntadi, Arif; Feriandi, Yudi (Institut Teknologi Garut, 2023)
To accommodate large amounts of data, a structured data warehouse is needed to produce more accurate information and support decision making for organizational stakeholders. To build a data warehouse, software such as Microsoft SQL Server can be used which has advantages in the aspects of data security, scalability, collaborative capabilities and extendability. Serial data on population, health personnel, economics and various continuous primary and secondary data can be uploaded into SQL Server so that it can be stored in a structured and periodic manner. Data stored in the database is processed using certain data mining algorithms to produce information, knowledge and wisdom. This data warehouse and data mining approach can be applied to various sectors, for example health. This research aims to apply a data warehouse and data mining approach to analyzing the ratio of health worker needs in West Java Province, Indonesia using a single moving average algorithm and semi-automatic classification using empirical statistics on SQL Server and SQL Server Agent as well as visualization using Microsoft Power BI. Classification based on forecasting analysis of population data and determining the health worker gap ratio was successful in finding patterns through data mining on SQL Server efficiently and easily visualized using Power BI. Thus, SQL Server can be one of the practical tools chosen for implementing sustainable data mining.